Devastating Gynecological Infections in Women with STAT3 Deficiency. (9th January 2020) - Redor, Alexis; Danion, François; Parize, Perrine; Chandesris, Olivia; Dbjay, Jonathan; Duréault, Amélie; Le Guenno, Guillaume; Cazorla, Celine; Vergnon-Miszczycha, Delphine; Bats, Anne Sophie; Bodemer, Christine; Hoarau, Cyrille; et al.
Abstract: We provide the first description of a series of 9 severe gynecological infections (mastitis and pelvic cellulitis) occurring in the French national cohort of women with STAT3 deficiency. Each episode had unique features in terms of clinical presentation, microbial documentation, location, treatment duration, and related persistent esthetic damage.